2021
DOI: 10.1101/2021.06.30.450498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STEM CELL TECHNOLOGY PROVIDES NOVEL TOOLS TO UNDERSTAND HUMAN VARIATION IN Plasmodium falciparum MALARIA

Abstract: Plasmodium falciparum interacts with several human cell types during their complex life cycle, including erythrocytes and hepatocytes. The enuclated nature of erythrocytes makes them inaccessible to genetic tools, which in turn makes studying erythrocyte proteins involved in malaria invasion and development particularly difficult. Here we overcome this limitation using stem cell technology to develop a universal differentiation protocol for in vitro derivation of erythrocytes from a variety of stem cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Indeed, rs1541252 and rs1541255 were found to be associated with mean corpuscular hemoglobin concentration in African-American children and parasitemia in malaria patients, respectively [29,40]. However, this hypothesis was recently challenged by Villegas-Mendez et al and Pance et al [41,42]. Pance et al reported that ATP2B4 deletion fully inhibited PMCA4 expression but had a very slight effect on the parasite growth in human stem cell-derived erythroid cells [42], whereas Villegas-Mendez et al demonstrated that ATP2B4 gene targeting did not alter parasitemia in mice infected by Plasmodium berghei but did protect mice by against cerebral malaria induced by Plasmodium berghei [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, rs1541252 and rs1541255 were found to be associated with mean corpuscular hemoglobin concentration in African-American children and parasitemia in malaria patients, respectively [29,40]. However, this hypothesis was recently challenged by Villegas-Mendez et al and Pance et al [41,42]. Pance et al reported that ATP2B4 deletion fully inhibited PMCA4 expression but had a very slight effect on the parasite growth in human stem cell-derived erythroid cells [42], whereas Villegas-Mendez et al demonstrated that ATP2B4 gene targeting did not alter parasitemia in mice infected by Plasmodium berghei but did protect mice by against cerebral malaria induced by Plasmodium berghei [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis was recently challenged by Villegas-Mendez et al and Pance et al [41,42]. Pance et al reported that ATP2B4 deletion fully inhibited PMCA4 expression but had a very slight effect on the parasite growth in human stem cell-derived erythroid cells [42], whereas Villegas-Mendez et al demonstrated that ATP2B4 gene targeting did not alter parasitemia in mice infected by Plasmodium berghei but did protect mice by against cerebral malaria induced by Plasmodium berghei [41]. Interestingly, PMCA1 expression was increased in ATP2B4 −/− mice [41].…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of the PMCA4b variants is still unclear in malaria, as other PMCA isoforms may have a compensatory role. However, a recent study searching for the genetic background of malaria susceptibility reported the generation of human induced pluripotent stem cells with knocked-out Basigin or ATP2B4 genes (Pance et al, 2021, preprint [17]) and demonstrated the altered susceptibility of the differentiated erythroid cells to Plasmodium infection in both cases. Another current study in mice with systemic knock-out of PMCA4 [18] indicated that in these KO mice, malaria infection has a more pronounced central nervous system effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, difficulties associated with variation between lines, persistence of embryonic and/or fetal haemoglobin, low rates of expansion, incomplete differentiation and poor enucleation as well as the complexity of protocols required to differentiate such cells have plagued the quest for iPSC generated red blood cells ( Dias et al., 2011 ; Trakarnsanga et al., 2014 ; Focosi and Pistello, 2016 ). Efforts to improve methodologies for the derivation of such lines and their subsequent differentiation remain a highly active area of research ( Bernecker et al., 2019 ; Hansen et al., 2019 ; Lim et al., 2021 ), however application of such lines for generation of cells suitable for malaria studies so far is extremely limited ( Pance et al., 2021 ).…”
Section: Sustainable Sources Of Erythroid Cellsmentioning
confidence: 99%
“…Where flow cytometry assays of parasitemia using nucleic acid staining dyes is routine for donor erythrocytes, the confounding nuclear signal where orthochromatic erythroblasts are studied prohibits this means of assessment and in the ideal situation where purified reticulocytes are studied residual RNA in reticulocytes necessitates careful controls ( Satchwell et al., 2019 ). Miniaturisation of assays and manual inspection of cytospin preparations ( Bei et al., 2010 ; Egan et al., 2015 ; Satchwell et al., 2019 ; Kanjee et al., 2021 ) have been powerful enablers of in vitro red blood cell use however efforts to adapt and improve flow cytometry based assessment through robust, nucleic acid labelling, use of fluorescent parasite lines ( Neveu et al., 2020 ), label free assessment of parasitemia ( Frita et al., 2011 ; Pance et al., 2021 ) or via advanced technologies such as Imaging Flow Cytometry ( Luiza-Batista et al., 2022a ) represent important endeavours. Ongoing efforts within the community of researchers seeking to improve and optimise in vitro erythroid culture enucleation rates, scalability and purification methods are of continued importance to improve accessibility ( Lim et al., 2021 ; Pellegrin et al., 2021 ; Gallego-Murillo et al., 2022 ).…”
Section: Challengesmentioning
confidence: 99%